A Study to Determine the Incidence of Drug Abuse Among Students of Tertiary Institutions. A Case Study Wukari - Umaru, Isaac John; Asare, Solomon Ossom; Omanchi, Emmanuel; Umogbai, Debora Akinola; Olayemi, Abimbola Gbenga; Dambazau, Zainab Bello; Chukwudi, Emmanuel Eluu; Jack, Precious Chioma (African Journal of Medicine, Surgery and Public Health Research, 2026)
This study explores the incidence, patterns, and consequences of drug abuse among students in tertiary institutions in Taraba State, Nigeria, using a mixed-methods approach. Quantitative survey data revealed that 28.4% of students had engaged in drug use, with alcohol (64.8%), cannabis (45.1%), and tramadol identified as the most commonly abused substances. Qualitative insights from focus group discussions and key informant interviews highlighted the social dynamics, institutional gaps, and cultural factors shaping substance use, with male students aged 21–25 and those living off-campus emerging as the most vulnerable demographic, while covert drug use among female students was linked to peer and romantic influences. Peer pressure, academic stress, and curiosity were reported as primary motivators, and hostel environments were found to foster experimentation. Drug abuse was associated with academic decline, mental health problems—including anxiety, depression, and suicidal ideation—and low utilization of counseling services, whereas institutional responses were characterized by limited drug education, weak enforcement, and poor awareness of available support systems. The study underscores the urgent need for integrated prevention strategies, peer-led interventions, and enhanced mental health services to address this growing public health concern.